1995
DOI: 10.1006/viro.1995.1237
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Molecular Characterization of Subtype D, G, and A/D Recombinant HIV-1 Transmissions in Sweden

Abstract: HIV-1 can be subdivided into at least nine genetic subtypes (A through H and O), but in Europe and the United States there is an almost complete dominance of subtype B. In this study three Swedish HIV-1 transmission chains of subtypes other than subtype B have been biologically and molecularly characterized. The three index cases were African men. The p17 gag and env V3 regions of the HIV-1 genome were directly sequenced from uncultured lymphocytes. Phylogenetic analyses showed that the HIV-1 variants with eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…HIV-1 isolates are classified into groups M, N, and O based on sequence identity; the vast majority of the isolates belong to group M, which is further divided into different subtypes (44). Recombination can occur between closely related strains (15,34,47,56), between isolates from different subtypes (4,5,10,33,43,49,55), or even between different HIV-1 groups (41,51). Currently, many of the circulating strains of HIV-1 are intersubtype recombinants (9,26,45,46).…”
Section: High Rates Of Hiv-1 Recombination and Their Implicationsmentioning
confidence: 99%
“…HIV-1 isolates are classified into groups M, N, and O based on sequence identity; the vast majority of the isolates belong to group M, which is further divided into different subtypes (44). Recombination can occur between closely related strains (15,34,47,56), between isolates from different subtypes (4,5,10,33,43,49,55), or even between different HIV-1 groups (41,51). Currently, many of the circulating strains of HIV-1 are intersubtype recombinants (9,26,45,46).…”
Section: High Rates Of Hiv-1 Recombination and Their Implicationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This has been the cause of some concern, in that although all HIV-1 subtypes appear to be equally susceptible to antiretroviral therapy 8 (ARV), different HIV-1 subtypes may differ in terms of syncytiainducing capacity, 9,10 rate of disease progression, pattern of ARV resistance, 11 and response to possible vaccine candidates. In Italy, the percentage of infection with non-B subtypes among HIV-seropositive people has been reported to range from 5.4% to 12.6%, and it exceeds 63% among foreigners living in Italy.…”
mentioning
confidence: 99%
“…Although these studies have found that the rate of recombination can be influenced by the nature of the target cell and that certain genomic regions may be hot spots for recombination, there is general agreement that recombination occurs frequently throughout the genome (2 to 20 events/genome/ replicative cycle) and has the capacity to rapidly shuffle genomic segments from parental viruses (21,27,46,54). Numerous viral strains derived through recombination between distinct HIV-1 subtypes have been identified in infected individuals, indicating that recombination also occurs in vivo (26,42,49), and studies performed using limiting-dilution PCR suggest that such events are occurring frequently (51; The advantages that accrue through recombination and the impact of recombination on HIV-1 pathogenesis in individual patients are not clearly defined (45). The shuffling of polymorphisms found in distinct viral quasispecies could play a role in generating viral diversity (33,45).…”
mentioning
confidence: 99%